Initial effects of anti-pronation tape on the medial longitudinal arch during walking and running. Issue 12 (23rd November 2005) - Vicenzino, B; Franettovich, M; McPoil, T; Russell, T; Skardoon, G
Abstract : Objectives: To investigate the effect of an augmented LowDye taping technique on the medial longitudinal arch of the foot during dynamic tasks such as walking and jogging, and to elucidate the relation between tape induced changes in static and dynamic foot posture. Methods: Seventeen subjects (mean (SD) age 27 (5.8) years) who were asymptomatic and exhibited a navicular drop greater than 10 mm were studied. Medial longitudinal arch height standardised to foot length during standing and at mid-stance of walking and jogging was measured from digital video images taken before and after the application of an anti-pronation taping technique. A no tape control condition was also included. Results: Compared with the no tape control condition, tape produced a significant mean (SD) increase in the medial longitudinal arch height index of 0.031 (0.015), 0.026 (0.014), and 0.016 (0.017) during standing, walking, and jogging respectively (p<0.05). The relative increase in medial longitudinal arch height represents an anti-pronation effect. The tape induced changes in the medial longitudinal arch height measured during standing correlated strongly with those measured during walking and jogging (Pearson's r = 0.7 and 0.76 respectively). Conclusions: The augmented LowDye tape was effective in controlling pronation during both static and dynamic activity. Tape induced changes in static foot posture paralleled those during walking and jogging.